2011
DOI: 10.1200/jco.2010.30.3552
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nuclear Localized and Tyrosine Phosphorylated Stat5 in Breast Cancer Predicts Poor Clinical Outcome and Increased Risk of Antiestrogen Therapy Failure

Abstract: A B S T R A C T PurposeTo investigate nuclear localized and tyrosine phosphorylated Stat5 (Nuc-pYStat5) as a marker of prognosis in node-negative breast cancer and as a predictor of response to antiestrogen therapy. Patients and MethodsLevels of Nuc-pYStat5 were analyzed in five archival cohorts of breast cancer by traditional diaminobenzidine-chromogen immunostaining and pathologist scoring of whole tissue sections or by immunofluorescence and automated quantitative analysis (AQUA) of tissue microarrays. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 40 publications
6
98
0
Order By: Relevance
“…Activated STAT5 was associated with a favorable prognosis in breast cancer patients [150]. Peck et al showed that a loss of pSTAT5 from the nucleus predicts for a poor clinical outcome along with the possibility of failure to respond to endocrine therapy in ER+ve breast cancer patients [151]. Interestingly, the expression of Bcl6 is inhibited by prolactin mediated activation of STAT5 in breast cancer [152].…”
Section: Role In Breast Cancermentioning
confidence: 99%
“…Activated STAT5 was associated with a favorable prognosis in breast cancer patients [150]. Peck et al showed that a loss of pSTAT5 from the nucleus predicts for a poor clinical outcome along with the possibility of failure to respond to endocrine therapy in ER+ve breast cancer patients [151]. Interestingly, the expression of Bcl6 is inhibited by prolactin mediated activation of STAT5 in breast cancer [152].…”
Section: Role In Breast Cancermentioning
confidence: 99%
“…The decrease of phosphorylated STAT5 is correlated with poorer patient survival and predicts both poor clinical outcome and increased risk of antiestrogen therapy failure (61)(62)(63)(64)(65). PRLR has been shown to suppress epithelial-mesenchymal transition and invasiveness of breast cancer cells (66), and PRLR expression is significantly down-regulated in invasive breast cancer, the down-regulation being associated with lymph node metastasis, lower tumor grade, and metastasis-free survival in breast cancer patients (67).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…As STAT3 has been the focus of cancer research, STAT3 inhibitors are being investigated, and a growing number of preclinical studies are ongoing. Therefore, more and more researchers have begun to focus on STAT5 (15)(16)(17)(18)(19). Evidence reveals that inhibition of STAT5 affects biological behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%